Early-Onset Neonatal Sepsis: Role of C-Reactive Protein, Micro-ESR, and Gastric Aspirate for Polymorphs as Screening Markers - Sukhdeep Kaur; Kunwarpal Singh (International Journal of Pediatrics)
Introduction. Early-onset neonatal sepsis is a major cause of morbidness and death in newborn children. Its timely diagnosis is usually a challenge in developing countries like India. Aim. To study the efficacy of C-reactive protein (CRP), micro-ESR, and gastric aspirate for polymorphs in the diagnosis of early-onset neonatal sepsis. Materials and Methods. This study included sixty term and preterm children, inborn and referred cases. The children who presented before day seven of life with clinical suspicion of sepsis or who were at high risk of developing sepsis were included. These were further investigated. Significant values for screening tests were taken as C−reactive protein>0.6 mg/dl, micro-ESR—after 1 hour, fall in the column of blood in capillary tube was measured, and result was taken as mm fall in 1 hr, and gastric aspirate for polymorphs>5 polymorphs/HPF. Sepsis screen positive result was 2 or more positive tests. The statistical evaluation was done using Fisher, and ANOVA tests using SPSS 20.0 version. Results. Sixty children were included in the study with forty as the referred ones. Most of them had tachypnea (45%). CRP showed high sensitivity, whereas micro-ESR and gastric aspirate for polymorphs showed high specificity. Conclusions. Neonatal sepsis screening is required for the detection of infection as the blood culture report may not be positive in all the cases, and even if positive, the result takes few hours. CRP showed high sensitivity, whereas micro-ESR and gastric aspirate for polymorphs showed high specificity independently as well as when combined.